The optimal inflation buffer with a zero bound on nominal interest rates - Roberto M. Billi (Goethe University Frankfurt, Center for Financial Studies (CFS), 2004)
This paper characterizes the optimal inflation buffer consistent with a zero lower bound on nominal interest rates in a New Keynesian sticky-price model. It is shown that a purely forward-looking version of the model that abstracts from inflation inertia would significantly underestimate the inflation buffer. If the central bank follows the prescriptions of a welfaretheoretic objective, a larger buffer appears optimal than would be the case employing a traditional loss function. Taking also into account potential downward nominal rigidities in the price-setting behavior of firms appears not to impose significant further distortions on the economy.
urn:nbn:de:hebis:30-10932
Keywords: C63; E31; E52; 330; Inflation Inertia; Downward Nominal Rigidity; Nonlinear Policy; Liquidity Trap